Digital competences of teachers in Lebanon: a comparison of teachers’ competences to educational standards - Levon Momdjian; Marni Manegre; Mar Gutiérrez-Colón (Research in Learning Technology, 2024)
The impact of digitalisation on everyday life has necessitated the need for learners to acquire digital competence as part of their education. In order to prepare students to become digital citizens, it has become necessary for teachers to acquire and implement digital competence in the classroom. This study applied the DigCompEdu framework to Lebanese schools and teachers to examine the digital competences of teachers and their alignment with Ministry of Education & Higher Education (MEHE) standards. This study followed a cross-sectional descriptive design and involved 170 in-service teachers in Lebanese schools. This study found that whilst schoolteachers’ practice meets all MEHE indicators, there is a significant need for training to schoolteachers in using digital tools and resources to promote collaboration in the learning process. The findings highlighted the importance of digital competences in schools and the need for ongoing training and support for teachers in this area.